Changing Dynamics of Bilateral Relations between US and Pakistan: Sino-Russia Factor - Ahmad, Farooq; Khalid, Iram (Annals of Human and Social Sciences, 2023)
This paper aimed at an exhaustive analysis of changing dynamics in bilateral relations between the US and Pakistan. Solid projections about the future shape of US-Pakistan relationship are integral part of this study. Qualitative method of research with descriptive and predictive approaches has been employed to analyze relevant material. Economic rise of China in recent times has expanded its clout. Russia appears to have recovered some of its lost space. These shifts have indelible imprints on the US relations with its allies especially Pakistan. Bilateral ties between Pakistan and America have always been transactional and uncertain. The post-evacuation scenario in Afghanistan has also raised doubts on the future of these relations. Whereas, Pakistan and China are neighbors who have close economic and security cooperation. Pakistan and Russia are also in process of healing old sores due to economic and geo-political needs. The US has shifted its weight in favor of India for strategic partnership in the region in its bid for containment of China. The changed scenario is beset with certain new avenues of benefits and threats at the same time